Strengths-based therapy : connecting theory, practice and skills - Jones-Smith, Elsie (Los Angeles : SAGE Publications, 2014)
Combining both the theory and practice of strengths-based therapy, Elsie Jones-Smith introduces current and future practitioners to the modern approach of practice -- presenting a model for treatment as well as demonstrations in clinical practice across a variety of settings. This highly effective form of therapy supports the idea that clients know best about what has worked and has not worked in their lives, helps them discover positive and effective solutions through their own experiences, and allows therapists to engage their clients in their own therapy. Drawing from cutting-edge research in neuroscience, positive emotions, empowerment, and change, this book helps readers understand how to get their clients engaged as active participates in treatment.
Preface -- Strengths-based therapy -- Human strengths theory : the neuroscience and relational components of strengths -- Strengths across cultures -- The strengths-based therapy model -- Strengths-based assessment -- Strengths-based recovery -- Strengths-based therapy and families -- Strengths-based therapy and recovery in mental health -- Strengths-based therapy, addiction, and a harm-reduction approach -- Strengths-based school counseling -- Strengths-based therapy and at-risk or at-promise youth -- Strengths-based therapy in correctional settings -- Strengths-based therapy and older adults -- Index.
Includes bibliographical references and index.
Keywords: Positive psychology; Psychotherapy -- methods; Resilience, Psychological; Psychotherapie